Politeness Strategies of Request In Ballerina Movie - Frina Diniarta Nur; Rafida Cesar Ratnasari (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2021)
This research aims to analyze politeness strategies of request found in the utterances in Ballerina movie. It intends to answer three (3) research questions, namely the types of politeness strategies of request, the reason of using the politeness strategies of request, and the relation among the characters that use politeness strategies of request in Ballerina movie. The theory used in analyzing the data is the theory of Brown and Levinson (1987). This research uses descriptive qualitative method. Fourteen (14) cases of politeness strategies of request are found. Five (5) data contain bald on record strategies, four (4) data contain positive politeness strategies, two (2) data contain negative politeness strategies, and three (3) data contain off record strategies. The reasons why the characters use a politeness strategy depend on the type of politeness strategy that they use. The reason why the characters use bald on record strategy is because they want the hearers to do what they want immediately. The reason why the characters use positive politeness strategy is because they do not attempt to keep their distance with the hearers. Then the reason why the characters use negative politeness strategy is because they intend to ask the hearers to do something in a polite way. Finally, the reason the characters use off record strategy is because they want the hearers to be sensitive in order to understand what the speakers want. Regarding the last research question, which is the relations among the characters, the result shows that this also varies. The relations of the characters who use politeness strategy of request can be between close friends, teacher and student, people who have the same age, people who just met, owner and worker, or family who are not close with each other.